Loose Parts and Picture Media on Kindergarten Children's Creativity and Speaking Skills - Sri Uning Puji Utami; Sujarwo Sujarwo (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Children's creativity and speaking skills can be influenced by several factors, including learning media. The purpose of this study was to determine and analyze the influence of loose parts media and picture media on children's creativity and speaking skills. The research used a quasi-experimental design with a nonequivalent control groups approach. The population consisted of group B children at PPBI Batik Kindergarten and Suryodiningratan Kindergarten, Kemantren, Mantrijeron, totaling 74 students. The sampling employed purposive sampling methods. The control group comprised group B1 at PPBI Batik Kindergarten with 15 children and group B2 at Suryodiningratan Kindergarten with 22 children. The experimental group from PPBI Batik Kindergarten was B2 with 15 children, and from Suryodiningratan Kindergarten was B1 with 22 children. The assessment instruments for creativity and speaking skills each used observation sheets covering four dimensions on a Likert scale from 1 to 5. The validity and reliability of the instruments were confirmed through expert judgment and empirical testing. The study concluded that Loose Parts media significantly impacts children's creativity and speaking skills. Likewise, picture media significantly affects these skills. Children who engaged in activities with Loose Parts media showed better creativity and speaking skills compared to those using picture media.